Pre - Programmed Chef - Mahdzar, Mazlina; Abdul Halim, Amira Alya; Mohd Fazli, Nur Fatin Nabiela; Mohd Agil, Nur Aisyah; Mohd Thahrir, Noor Fazlina; Anak Ragai, Wendy (Multidisciplinary Applied Research and Innovation, 2021)
Preprogrammed Chef is a new era of digital technology application of food and beverage (Digital Food & Beverage). The program is an advanced technology application to help upgrade food and beverage service. This program is designed to minimize human interaction due to our continuous battle with the pandemic. The auto features that are being applied in this idea are to help ease any discomfort or trouble that are experienced by the customers at any food and beverage establishment. The machine will be programmed in detail to complete tasks like taking customer’s orders, cooking the food, packing prepared food and serve complete food to the customer. Therefore, with the idea that combining food and beverage and technology, the desire is to give new hopes in the future of food and beverage businesses